2018
DOI: 10.1016/j.jcmg.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Noncontrast Myocardial T1 Mapping by Cardiac Magnetic Resonance Predicts Outcome in Patients With Aortic Stenosis

Abstract: High native T1 value on noncontrast T1 mapping CMR is a novel, independent predictor of adverse outcome in patients with significant AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 38 publications
1
72
0
2
Order By: Relevance
“…29,30 Therefore, clinical outcomes in these patients are most likely determined by the myocardial dysfunction regardless of the AVR approach. Higher mortality rate in patients with AS has been reported to be associated with increased myocardial fibrosis detected by cardiac magnetic resonance imaging 31 regardless of AVR strategies. 29 Future studies with cardiac magnetic resonance imaging would be able to prove the larger amount of myocardial fibrosis in patients with lower LVEF and/or SVI among patients with AS.…”
Section: Patients With Preserved Lvef But Decreased Svimentioning
confidence: 99%
“…29,30 Therefore, clinical outcomes in these patients are most likely determined by the myocardial dysfunction regardless of the AVR approach. Higher mortality rate in patients with AS has been reported to be associated with increased myocardial fibrosis detected by cardiac magnetic resonance imaging 31 regardless of AVR strategies. 29 Future studies with cardiac magnetic resonance imaging would be able to prove the larger amount of myocardial fibrosis in patients with lower LVEF and/or SVI among patients with AS.…”
Section: Patients With Preserved Lvef But Decreased Svimentioning
confidence: 99%
“…Wong et al found, in an unselected cohort of patients undergoing cardiac MRI, that ECV is a strong predictor of mortality . Several studies in AS patients have shown that T 1 values and the degree of myocardial fibrosis correlate with disease progression and mortality and that myocardial ECV is a strong predictor of cardiovascular complications (Fig. ).…”
Section: Tissue Characterization and Myocardial Function Assessment Bmentioning
confidence: 99%
“…T 1 values are a marker for myocardial fibrosis or tissue inflammation: important markers of disease progression in patients with left‐sided VHD. In AS patients, mechanisms leading to myocardial fibrosis include diffuse ischemia in hypertrophic LV myocardium as a consequence of chronic pressure overload . In AR and MVR, volume overload causes activation of the renin‐angiotensin‐aldosterone system, which activates profibrotic pathways in the myocardium .…”
Section: Tissue Characterization and Myocardial Function Assessment Bmentioning
confidence: 99%
“…14,17 In addition, the presence of myocardial fibrosis identified by cardiac MRI has been shown to be independently associated with mortality in patients with AS despite preserved LVEF. [18][19][20][21] These parameters could expand and potentially improve the proposed AS staging system, but are not currently incorporated into the routine clinical assessment of such patients.…”
Section: Future Directionsmentioning
confidence: 99%